2014
DOI: 10.1186/1471-2466-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of arterial stiffness in COPD

Abstract: BackgroundCardiovascular morbidity and mortality is high in patients with chronic obstructive pulmonary disease (COPD) and arterial stiffness is a potentially modifiable risk factor with added predictive value beyond that obtained from traditional risk factors. Arterial stiffness has been the target of pharmacologic and exercise interventions in patients with COPD, but the effects appear limited to those patients with more significant elevations in arterial stiffness. We aimed to identify predictors of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 30 publications
2
62
0
3
Order By: Relevance
“…Mills et al demonstrated that the patients with COPD had increased arterial stiffness compared with ageand smoking-matched controls (21). Bhatt et al demonstrated that the aortic PWV values may be an important predictor of CVD for the patients with COPD (22). In a review by Maclay et al (23) of men without cardiovascular disease, a relationship between reduced pulmonary function and increased PWV was found, independent of the traditional risk factors for cardiovascular disease, such as smoking, hypercholesterolemia, and hypertension (24).…”
Section: Discussionmentioning
confidence: 99%
“…Mills et al demonstrated that the patients with COPD had increased arterial stiffness compared with ageand smoking-matched controls (21). Bhatt et al demonstrated that the aortic PWV values may be an important predictor of CVD for the patients with COPD (22). In a review by Maclay et al (23) of men without cardiovascular disease, a relationship between reduced pulmonary function and increased PWV was found, independent of the traditional risk factors for cardiovascular disease, such as smoking, hypercholesterolemia, and hypertension (24).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of CAS is closely represented by pulmonary surfactant generated from Type II cells in the alveoli 2223 . From the alveolar spaces, pulmonary surfactant is carried up the airways due to the surface tension gradient and the mucociliary escalator 22, 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Local production and release of phospholipids by tracheal epithelial cells 2526 and the submucosal glands of both human tracheal and bronchial biopsy specimens 27 have also been detected, thus both sources likely contribute to airway surfactant composition. While evidence pertaining to the origin of the CAS points to both alveolar and local sources 12, 28 , recent studies suggest that alveolar surfactant represents the largest proportion of CAS 2223 . CAS phospholipids, quantified by analysis of raw tracheal aspirates, are composed of approximately 72–80% phosphatidylcholine (PC) and 33–45% dipalmitoylphosphatidylcholine (DPPC), with smaller amounts of phosphatidylglycerol (PG, 3–4%), phosphatidylethanolamine (PE, 12–15%), phosphatidylinositol (PI, 3–5%), and sphingomyelin (SPH, 2–4%) present 2223 .…”
Section: Methodsmentioning
confidence: 99%
“…По данным A. C. Aykan и соавт., у больных ХОБЛ сердечнолодыжечнососуди стый индекс, отражающий истинную жесткость арте рий, не зависящую от АД, был значительно увеличен и коррелировал с ОФВ 1 , индексом Тиффно и стадией ХОБЛ [15]. В мультицентровом рандомизированном исследовании, как было представлено в публикации S. P. Bhatt и соавт., у больных ХОБЛ СПВ в аорте была взаимосвязана не только с возрастом, уровнем САД, статусом курения, индексом кальцификации аорты, но и с ОФВ 1 по данным спирометрии [16].…”
Section: Discussionunclassified